AtFB meets LHC - Hewett, JoAnne; Shelton, Jessie; Spannowsky, Michael; Tait, Tim M. P.; Takeuchi, Michihisa (Physical review. D, Particles, fields, gravitation, and cosmology, 2011)
The recent Tevatron measurement of the forward-backward asymmetry of the top quark shows an intriguing discrepancy with Standard Model expectations, particularly at large t¯t invariant masses. Measurements of this quantity are subtle at the LHC, due to its pp initial state, however, one can define a forward-central-charge asymmetry which captures the physics. We study the capability of the LHC to measure this asymmetry and find that within the SM a measurement at the 5σ level is possible with roughly 60 fb−1 at √s=14 TeV. If nature realizes a model which enhances the asymmetry (as is necessary to explain the Tevatron measurements), a significant difference from zero can be observed much earlier, perhaps even during early LHC running at √s=7 TeV. We further explore the capabilities of the 7 TeV LHC to discover resonances or contact interactions which modify the t¯t invariant mass distribution using recent boosted top-tagging techniques. We find that TeV-scale color-octet resonances can be discovered, even with small coupling strengths and that contact interactions can be probed at scales exceeding 6 TeV. Overall, the LHC has good potential to clarify the situation with regards to the Tevatron forward-backward measurement.
Gesehen am 21.09.2022
Das t in AtFB ist hochgestellt, FB ist tiefgestellt